Mental Training and Anxiety: Examining the Moderating Role of Gender in Athletes - Duyan, Mehdi; Celik, Talip; Karatas, Ozgur; Ilkim, Mehmet; Karatas, Emine Ozturk; Yavuz, Cumaali; Ruzgar, Kerim (Univ Illes Balears, 2024)
This study aimed to examine how gender may influence the relationship between mental training practices and anxiety levels in both individual and team athletes. Using a quantitative approach, data was gathered through convenience sampling using electronically administered questionnaires. A grand total of 348 athletes from secondary school, high school, and university teams in individual and team sports across four Turkish provinces took part in the event. The Mental Training Scale developed by Behnke et al. (2019) was used to evaluate mental training practices, while the Sports Anxiety Scale -2, created by Smith et al. (2006) and Smith, Smoll and Schutz (1990), was used to gauge levels of anxiety. The data analysis included various statistical techniques such as descriptive statistics, Cronbach's alpha for assessing scale reliability, confirmatory factor analysis, correlation analysis to explore variable relationships, and bootstrap regression analysis to investigate the potential moderating effect of gender. The results showed that the predictor variables together explained about 9% of the variation in anxiety (R-2 = .084). There was a noteworthy correlation between mental training practices and anxiety, with mental training practices showing a beneficial impact beta = .30, p < .05). Additionally, gender was found to have a significant influence in a positive direction beta = 1.58, p < .001). In addition, a noteworthy moderating effect was found, suggesting that gender plays a role in the connection between mental training and anxiety beta = -.37, p < .001). It appears that female athletes on school teams are more inclined to incorporate mental training practices into their routines, leading to better anxiety management compared to male athletes who do not engage in such practices.
Keywords: Mental Training; Anxiety; Gender in Athletes